Mechanochemical synthesis of N-doped porous carbon at room temperature - Casco, Mirian Elizabeth; Kirchhoff, Sebastian; Leistenschneider, Desiree; Rauche, Marcus; Brunner, Eike; Borchardt, Lars (Nanoscale, 2019)
We report the one-pot mechanochemical synthesis of N-doped porous carbons at room temperature using a planetary ball mill. The fast reaction (5 minutes) between calcium carbide and cyanuric chloride proceeds in absence of any solvent and displays a facile bottom-up strategy that completely avoids typical thermal carbonization steps and directly yields a N-doped porous carbon containing 16 wt% of nitrogen and exhibiting a surface area of 1080 m2 g-1.
CRIS-Team Scopus Importer:2022-04-14